New spatial practices in organised sport following COVID-19: the Swedish case - Book, K.; Hedenborg, S.; Andersson, K. (Sport in Society: Cultures, Commerce, Media, Politics, 2022)
Following the outbreak of COVID-19 in 2020, the majority of European countries imposed lockdowns, whereas Sweden introduced comparatively moderate constraints. The Public Health Agency of Sweden stated that sports and physical activity could continue if conducted `safely` and recommended outdoor activities. This article aims to identify new spatial practices and strategies developed by organised recreational sport providers (i.e. sport clubs, commercial providers) following the outbreak of the pandemic. Further, it identifies obstacles and opportunities for new spatial solutions, as well as possible long-term (lasting) effects of the strategies imposed. Also, it discusses these obstacles and opportunities in relation to contemporary sport facility challenge. The data draws upon 24 semi-structured interviews with sport coaches and leaders. All interviews were transcribed verbatim and analysed using a thematic analysis. The results suggest that most respondents show adaptability by moving their activities outdoors. Generally, for-profit organisations have been more innovative and adaptive. Obstacles for new spatial solutions include localisation, weather, (perceived) need of equipment, leadership, competing interests in public space, and notably the perception of what sport is. Positive examples of spatial adaptability show that there is a potential for sport providers to open up for different spatial solutions and more flexibility in relation to their activities, in order to ease the pressure on formal indoor (and, to some extent, outdoor) sport facilities while amending the perception of sport activities.